The Concept ff Handling Overcapacity in Prison Through A Restorative Justice Approach to Drug Abusers - Widya Sari, Nani; Yanto, Oksidelfa; Prakash Nunna, Bhanu; Azis, Abdul (Pamulang Law Review, 2023)
The implementation of the coaching carried out by Prison for the inmates often becomes not optimal due to the complexity of the problems that occur within Prison. One of the root causes of issues at Prison is overcapacity. This paper then tries to see by analyzing the nature of narcotics crime as a particular crime and Indonesia's role in overcoming narcotics crime. Then also visit and explore the implications of overcapacity in Prison and concepts that can be applied to prevent overcapacity in Prison. The research method used in this paper is a normative juridical research method, with the data source used being secondary data obtained through library research. The study results indicate that narcotics crime as a particular crime is transnational and involves international crime organizations. Indonesia's role in overcoming narcotics crime can be seen from the regulation in Law Number 35 of 2009. In this regulation, sellers and dealers are given a high penalty, even death. Sentences should not be given to those who are called victims or addicts. The implications of overcapacity in Prison can result in non-optimal coaching due to the complexity of the problems that occur in Prison. Overcapacity is one of the root causes of issues at Prison. For this reason, it is necessary to apply a concept to prevent overcapacity from occurring in Prison by providing rehabilitation as a form of using restorative justice.